1989
DOI: 10.1177/019459988910000102
|View full text |Cite
|
Sign up to set email alerts
|

Natural History vs. Surgery for Meniere's Disease

Abstract: Menière's disease has an episodic course, and certain patients undergo spontaneous remission of their vertigo. A retrospective study of patients treated from 1974 to 1983 was undertaken to evaluate the long-term outcome of patients with Menière's disease for whom surgery was recommended, comparing those who had a surgical procedure with a similar group of patients who declined surgery. The surgical procedures performed were endolymphatic subarachnoid shunt (ELS), retrolabyrinthine vestibular neurectomy (RVN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
5

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(102 citation statements)
references
References 8 publications
3
93
1
5
Order By: Relevance
“…Approximately the same results were obtained by Silverstein et al [10] in a control group of patients who declined surgery. These authors who concluded that endolymphatic sac surgery does not alter the natural course of vertigo control in Ménière’s disease.…”
Section: Discussionsupporting
confidence: 79%
“…Approximately the same results were obtained by Silverstein et al [10] in a control group of patients who declined surgery. These authors who concluded that endolymphatic sac surgery does not alter the natural course of vertigo control in Ménière’s disease.…”
Section: Discussionsupporting
confidence: 79%
“…Multiple studies have found progressive reduction in vertigo spells leading to complete recovery within 2 years from onset [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…For those 97 subjects with follow-up data at or beyond 2 years, the remission rate (needing no further intratympanic treatments) was 70%. Before the advent of intratympanic therapies, Silverstein et al (17) studied a group of patients with Ménière's disease who had failed medical therapy and were offered endolymphatic sac surgery or vestibular neurectomy. Of their 50 patients who declined any surgery, 57% had complete control of vertigo after 2 years, and 70% had complete control after 8.3 years.…”
Section: Discussionmentioning
confidence: 99%